DAMPAK PROGRAM PUAP TERHADAP PENDAPATAN PETANI JAGUNG MARERIS DI DESA KAWANGKOAN KECAMATAN KALAWAT - Imanuel Sugandi Rompas; Joachim N.K. Dumais; Celcius ., Talumingan (Sam Ratulangi University, 2017)
The purpose of this study was to compare the income of Mareris corn farmers before and after receiving the PUAP program in Kawangkoan Village, Subdistrict Kalawat, North Minahasa Regency. The benefit of this research is as a reference material to increase the income of farmer’s corn.This research takes 3 (three) months starting from June 2016 in Kawangkoan Village, Kalawat Subdistrict. Method of data retrieval used in this research is primary data and secondary data. The primary data were obtained from interviews of farmers belonging to Marerist group. Secondary data is supporting data obtained from agricultural extension officer. Sampling is done by using the quota of 15 peasants. The results showed that at a confidence level α = 5%, tcount = 7.628 > ttable = 2.145 so H0 was rejected and H1 accepted. Thus there are differences in income of corn farmers before and after receiving PUAP the program.